Analisis Kepatuhan Prinsip-Prinsip Syariah Terhadap Kesehatan Finansial Dan Fraud pada Bank Umum Syariah - Marheni, Marheni (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2017)
This aim of study were to determine the effect of Islamic income on financial health of sharia banks; To know the effect of financing profit sharing on financial health of sharia banks; To determine the effect of Islamic income on the fraud of sharia banks; To know financing profit sharing on fraud of sharia banks and to determine the effect financial health on fraud of sharia banks. The population research were all sharia banks in Indonesia. Selected samples were 8 sharia banks. Analysis method used path analysis. The results showed that Islamic income had positive and significant effect on financial health, financing profit sharing had positive and significant effect on financial health. Islamic income had a negative and significant effect on fraud. Shared financing had a negative and significant effect on fraud. Financial health hada positive and significant effect on fraud.